The tonoplast-associated citrate binding protein (CBP) of Hevea brasiliensis. Photoaffinity labeling, purification, and cloning of the corresponding gene - Rentsch D; Amrhein N; Gorlach J; Martinoia E; Vogt E (Journal of Biological Chemistry, 1995)
A detailed comparison of citrate uptake into the vacuole-like lutoids of rubber tree (Hevea brasiliensis) and of malate and citrate transport into barley (Hordeum vulgare) vacuoles revealed very similar transport specificities. In order to idetify proteins mediating the transport, two photoreactive analogues (N-(2-hydroxy-5-azido)-diazo-N-3,5-benzenedicarboxylic acid and 5-azidoisophythalic acid) of malate/citrate were synthesized and found to efficiently inhibit citrate uptake into barley vacuoles (Ki= 18 mM) and Hevea lutoid vesicles (Ki= 27 mM). In vacuoles from both plant species, these photoaffinity probes specifically labelled a single protein with a molecular mass of 26.6 kDa. This citrate binding protein (CBP) was purified to homogeneity from Hevea lutoids, and amino acid sequences were determined for NH2-terminal and tryptic peptides. Using degenerate oligonucleotides of the NH2-terminal sequence, a cDNA coding for the CBP protein was isolated. The cDNA codes codes for a precursor protein of 238 amino acids, containing an NH2-terminal 31-amino acid signal sequence for endoplasmic reticulum targeting, a prerequisite for vacuolar localization. The mature CBP does not show significant similarities to any known primary protein structure and thus represents a member of a novel class of proteins. The nucleotide sequence has been submitted to the GenBank/EMBL database under accession number X89855.
Source Year: 1996
Keywords: Cloning; Hevea brasiliensis; Photoaffinity labelling